EFISIENSI SALURAN PEMASARAN KEMIRI (ALEURITES MOLUCCANA) PADA KELOMPOK TANI HUTAN WAHANA KAWASAN DI HUTAN KEMASYARAKATAN GUNUNG SASAK, KABUPATEN LOMBOK BARAT - Juansyah, Raj’i Waldi; Setiawan, Budhy; Lestari, Andi Tri (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2024)
Mount Sasak Community Forest (HKm) has the potential that can be utilized by the surrounding community through the utilization of Non-Timber Forest Products (NTFPs). The Wahana Kawasan Forest Farmer Group (KTH) is one of the groups that utilizes and manages NTFPs in the form of candlenuts in the Mount Sasak HKm. In the production and utilization activities of candlenut, it will focus on marketing channels as a form of effort made by a person or marketing institution to achieve a level of marketing success. The method used in this research is descriptive with a total of 32 respondents. The sampling technique was carried out by purposive sampling method. Determination of the number of respondents for intermediary traders is determined by the snowball sampling method. The results showed that there were 2 marketing channels. The marketing margin of marketing channels 1 and 2 has the same value of Rp. 2,000/kg. Meanwhile, the farmer's share obtained by marketing channel 1 amounted to 67% and marketing channel 2 amounted to 83%. The level of marketing efficiency in channel 1 of 7.8% indicates a less efficient marketing channel and marketing channel 2 of 3.7% indicates an efficient marketing channel.